Processes driving thunderstorms over the Agulhas Current. Issue 5 (14th March 2013) - de Boer, Agatha M.; Collier, Andrew B.; Caballero, Rodrigo
Abstract : [1] Lightning occurs predominantly over land and is not common over the open ocean. We study here one oceanic region in which thunderstorms are frequently found, namely the warm Agulhas Current off the southeast coast of South Africa. The seasonal and interannual lightning variability is derived from satellite and terrestrial data sets. Favorable climatic conditions for lightning are investigated using both ERA‐Interim and NCEP/NCAR reanalysis data. We find peak lightning in austral autumn over the Agulhas Current but with low seasonality (i.e., there is considerable lightning throughout the year). While the climatological wind direction varies strongly with latitude and season, the wind direction is predominantly northerly throughout the region during thunderstorms. A composite of sea level pressure during thunderstorm days indicates that thunderstorms are related to eastward‐propagating synoptic‐scale wave trains passing through the Agulhas Current region. The strong convective activity during thunderstorms occur in the warm sector of a cyclone and is associated with horizontal convergence and lifting of warm, moist surface air originating over the warm Agulhas Current. Key Points: Lightning over the Agulhas Current is strongly associated with cyclonic activity Lightning occurs in the warm sector of the cyclone from northerly moist winds Cyclones can form from cut‐off or coastal lows.